Ethical-Medical Orientations for the Attention of Critical Patients in the Covid-19 Pandemic Context - Aurenque-Stephan, D (Universitat Ramon Llull, 2021)
In the face of a possible health saturation due to the pandemic caused by the SARS-CoV2 coronavirus, the present paper wants to contribute with some guidelines in order to provide ethical orientation to prioritize patients and maximize the benefits for the majority of the population. This paper aims to generate an acceptable, consistent, and reasonable ethical framework to support the difficult work that health professionals will have in emergency rooms and intensive care units. The criteria and reflections in this paper aim to respect not only ethical-medical principles that focus their efforts on a particular patient, but especially on a broader public health ethics based on the principle of justice. Prioritization is therefore oriented in a utilitarian framework that seeks to save the largest number of lives, of life-years and considering the life stage, without neglecting the people’s dignity. In this sense, it is not only a matter of considering epidemiological criteria, but also of establishing socially acceptable ethical criteria. This proposal is a collective effort to bring together the comparative experience of various international ethical recommendations, adapting them, if pertinent, to the Chilean reality. © 2021 Authors. All rights reserved.